In situ observations of ClO in the Arctic Stratosphere - ER-2 aircraft results from 59 deg N to 80 deg N latitude - Brune, W. H.; Toohey, D. W.; Anderson, J. G.; Chan, K. R. (1990)
Large abundances of ClO were observed inside the Arctic polar vortex during 14 flights of the NASA ER-2 aircraft from Stavanger, Norway (59 deg N, 6 deg E) to 80 deg N latitude. Flights were conducted at altitudes between 14 and 20 km when the solar zenith angle was between 79 and 101 deg. Data are reported for three flights that represent the main features observed during the mission. These data, comparable to those obtained in the Antarctic ozone hole, indicate that the springtime Arctic polar vortex was extensively perturbed by heterogeneous chemistry and contained enough ClO to catalytically destroy ozone rapidly.